Synthesis, characterization, and antibacterial activity of a novel hybrid material layered double hydroxide doped by diaminododecylphosphonic acid (Bangladesh Journal of Pharmacology, 2025)
A novel hybrid material Zn/Al-diaminododecylphosphonic acid (DADPHA) layered double hydroxide (LDH) was synthesized and characterized for its structural, electronic, and antibacterial properties. X-ray diffraction confirmed DADPHA intercalation, increasing basal spacing from 7.55 to 7.95 angstrom. The crystallite size of Zn/Al-DADPHA (11.10 nm) was smaller than that of Zn/Al-SO₄ LDH (16.70 nm), indicating modification. FTIR confirmed phosphonic acid functional groups, while SEM revealed a morphological shift from hexagonal platelets to aggregated structures. Zn/Al-DADPHA exhibited significant antibacterial activity, with inhibition zones of 25.6 mm (Escherichia coli), 10.9 mm (Pseudomonas aeruginosa), 30.2 mm (Staphylococcus aureus), and 25.5 mm (Bacillus cereus). Molecular docking revealed strong ligand-protein interactions (-7.1 to -9.4 kcal/mol). DFT calculations showed a HOMO-LUMO gap of 4.82 eV, confirming electronic stability. MD simulations over 100 ns indicated complex stability with RMSD below 2.5 angstrom. These findings highlight the potential of Zn/Al-DADPHA LDH for biomedical and antimicrobial applications.